Review on the Relationship between Nano Modifications of Geopolymer Concrete and Their Structural Characteristics - Shilar, Fatheali A; Ganachari, Sharanabasava V; Patil, Veerabhadragouda B.; Khan, T. M. Yunus; Almakayeel, Naif Mana; Alghamdi, Saleh (MDPI, 2022)
The main objective of this review is to study some important nanomaterials and their impact on the performance of geopolymer concrete. This paper is an investigation into trends and technology in the development of different nanomaterials to develop higher structural performance geopolymer concrete. The effect of the alkaline to binder and sodium silicate to sodium hydroxide ratio on the performances of geopolymer performances is studied. The relationship between setting time and slump is evaluated through the ternary plot, the variation in compressive strength values is evaluated using the kernel density plot, and the relationship between split tensile and flexural strength is investigated using the scattering interval plot. Regression analysis is carried out among water absorption and bulk-density result values obtained from previous literature. As the molarity and alkaline to binder (A/B) ratios increase, the strength development of geopolymer concrete increases up to a specific limit. The addition of a small quantity of nanomaterials, namely, nano silica, nano alumina, carbon nano tubes, and nano clay, led to the maximum strength development of geopolymer concrete. Incorporating these nanomaterials into the geopolymer significantly refines the structural stability, improving its durability. The various products in GP composites emerging from the incorporation of highly reactive SEM, XRD, and FTIR analysis of nanomaterials reveal that the presence of nanomaterials, which enhances the rate of polymerization, leads to better performance of the geopolymer.
Přehled vztahu mezi nano modifikacemi geopolymerního betonu a jejich strukturálními charakteristikami
Keywords: nanomaterials; geopolymer concrete; compressive strength; SEM; XRD